Numerical Investigation on Air–Water Two-Phase Flow of Jinping-I Spillway Tunnel - Xiaoqun Wang; Jijian Lian (Applied Sciences, 2022)
Spillway tunnels are key features in the regulation of the water surface of a reservoir and in ensuring the safety of life and properties of people downstream in a high dam project. This research aimed to provide a better understanding of the ventilation mechanism. The air–water two-phase flow was simulated under the Euler–Euler framework. A hybrid drag model, which was verified by the prototype data of Jinping-I spillway tunnel, was proposed to improve the prediction of air demand and air entrainment. The air demand prediction error was less than 18.9%, while the air entrainment prediction error was less than 28.35%. On the basis of the new drag model, the air entrainment behind aerators, air velocity distribution in the air ducts, and the residual space of the tunnel were systematically analyzed. Two flow patterns of the ventilation system were finally summarized.